Quality of Randomized, Controlled Trials Published in Our National Journals - Salih ÖZGÖÇMEN, (Archives of Rheumatology, 2011)
Turkish physiatrists have an increasing contribution to the scientific literature in the field of musculoskeletal medicine. In recent years, two well-known national journals initiated by Turkish physiatrists (The Turk J Physical Med Rehabil and Turk J Rheumatol) have been covered by leading abstracting/indexing databases such as Science Citation Index-Expanded, Scopus, EBSCO and EMBASE. This development has caused a marked increase in submissions both qualitatively and quantitatively. Randomized controlled trials (RCTs) are considered to be the “gold standard” for assessing the effectiveness of pharmacological and other interventions and also represent the best evidence in physiatry practice.[<r1>,<r2>] Although the overall quality of RCTs reported in these journals have improved over time, reporting of key methodological issues still remains a problem. Herein, we would like to draw attention to the importance of the methodological quality of the randomized controlled trials published in the recent two years. In 2009 and 2010, these journals published five uncontrolled interventional trials [<r3>-<r7>] and 11 controlled trials.[<r8>-<r19>] One of the major problems of the RCTs was the insufficient information regarding the method of randomization and allocation concealment. RCTs with an unclear generation of the allocation sequence, allocation concealment and double blinding frequently overestimate intervention efficacy. Another problem was insufficient information regarding sample size estimation and power analysis. To conduct a systematic review and meta-analysis, searches are performed over the major databases such as Medline, Web of Science, etc. using the abstracts of the papers. Hence, it is essential to use terms like randomized, controlled, single- or double-blind, as well as prospective or placebo in the abstracts and titles of reports. The majority of the RCT reports in these journals miss these relevant terms as well as titles in their abstracts which increases the possibility of detecting them during the search procedure. Authors need to pay closer attention to the rigorous implementation and reporting of important methodological safeguards against bias in randomized trials. To achieve this, investigators and editors developed the original CONSORT (Consolidated Standards of Reporting Trials) statement to alleviate the problems arising from inadequate reporting of randomized controlled trials (RCTs). The recent publication of the CONSORT 2010 Statement now makes the previous version, CONSORT 2001 Statement, outdated. All authors are strongly recommended to refer to this most up-to-date version while writing or interpreting reports of clinical trials. Declaration of conflicting interests The author declared no conflicts of interest with respect to the authorship and/or publication of this article. Funding The author received no grant support for the research and authorship of this article.